Observations from a prospective small cohort study suggest that CGRP genes contribute to acute posttraumatic headache burden after concussion - La Fountaine, Michael F.; Hohn, Asante N.; Leahy, Caroline L.; Weir, Joseph P.; Testa, Anthony J. (Frontiers in Neurology, 2022)
Introduction: Post-traumatic headache (PTH) is commonly reported after concussion. Calcitonin gene-related peptide (CGRP) is implicated in the pathogenesis of migraine. We explored how single nucleotide polymorphisms (SNPs) from CGRP-alpha (CALCA) and the receptor activity modifying protein-1 (RAMP1) related to headache burden during the first week after concussion. Methods: A prospective study was performed in 34 collegiate athletes who sustained a concussion. Participants completed the symptom evaluation checklist from the SCAT3 within 48 hours of injury (V1), and again 4 (V2) and 7 (V3) days after injury. For each visit, the self-reported score (0-6) for headache, pressure in head, blurred vision, and sensitivity to light/noise were reported and summed to calculate the headache burden. A saliva sample was obtained and genotyped for CALCA (rs3781719) and RAMP1 (rs10185142). RAMP1 (TT, TC, CC) and CALCA (AA, AG, GG) were dichotomized (A+, A- and T+, T-, respectively) and concatenated (T+A+, T+A-, T-A+, T-A-) for analyses. Results: Headache Burden at Visit 1 was greatest in T+A+ compared to T-A+, and trended toward a significant difference with T+A-. Repeated-measures ANOVA revealed the presence of significant visit main effects (p<0.001, η2= 0.404), but the group (p=0.055) and interaction effects only trended (p=0.094). Pearson’s χ2 tests revealed that 88% of those with return-to play (RTP) exclusions ≥15 days had PTH with multi-sensory symptoms (PTH+SENS) as compared to 35% in those with RTP <14 day. Conclusion: Knowledge of RAMP1 and CALCA genotypes appear to improve an understanding the presenting features and magnitude of headache burden after concussion injury.